The TRPV4 Agonist GSK1016790A Regulates the Membrane Expression of TRPV4 Channels - Baratchi, Sara; Keov, Peter; Darby, William G.; Lai, Austin; Khoshmanesh, Khashayar; Thurgood, Peter; Vahidi, Parisa; Ejendal, Karin; McIntyre, Peter (Frontiers in Pharmacology, 2019)
TRPV4 is a non-selective cation channel that tunes the function of different tissues including the vascular endothelium, lung, chondrocytes and neurons. GSK1016790A is the selective and potent agonist of TRPV4 and a pharmacological tool that is used to study the TRPV4 physiological function in vitro and in vivo. It remains unknown how the sensitivity of TRPV4 to this agonist is regulated. The spatial and temporal dynamics of receptors are the major determinants of cellular responses to stimuli. Membrane translocation has been shown to control the response of several members of the transient receptor potential (TRP) family of ion channels to different stimuli. Here, we show that TRPV4 stimulation with GSK1016790A caused an increase in [Ca2+]i that is stable for a few minutes. Single molecule analysis of TRPV4 channels showed that the density of TRPV4 at the plasma membrane is controlled through two modes of membrane trafficking, complete and partial vesicular fusion. Further, we show that the density of TRPV4 at the plasma membrane decreased within 20 min, as they translocate to the recycling endosomes and that the surface density is dependent on the release of calcium from the intracellular stores and is controlled via a PI3K, PKC and RhoA signalling pathway.